Questionnaire - Australia. Department of Social Security (1975)
Copy of survey sent to users of the bulletin "Benefits, policy and review division, four-weekly summary of statistics".
Manuscript reference: NLA MS 5008.
Keywords: Public welfare -- Australia -- Statistics